Gift from Nature: Cyclomarin A Kills Mycobacteria and Malaria Parasites by Distinct Modes of Action. Issue 17 (16th October 2015) - Bürstner, Nathalie; Roggo, Silvio; Ostermann, Nils; Blank, Jutta; Delmas, Cecile; Freuler, Felix; Gerhartz, Bernd; Hinniger, Alexandra; Hoepfner, Dominic; Liechty, Brigitta; Mihalic, Manuel; Murphy, Jason; et al.
Abstract: Malaria continues to be one of the most devastating human diseases despite many efforts to limit its spread by prevention of infection or by pharmaceutical treatment of patients. We have conducted a screen for antiplasmodial compounds by using a natural product library. Here we report on cyclomarin A as a potent growth inhibitor of Plasmodium falciparum and the identification of its molecular target, diadenosine triphosphate hydrolase (PfAp3Aase), by chemical proteomics. Using a biochemical assay, we could show that cyclomarin A is a specific inhibitor of the plasmodial enzyme but not of the closest human homologue hFHIT. Co‐crystallisation experiments demonstrate a unique binding mode of the inhibitor. One molecule of cyclomarin A binds a dimeric PfAp3Aase and prevents the formation of the enzyme⋅ substrate complex. These results validate PfAp3Aase as a new drug target for the treatment of malaria. We have previously elucidated the structurally unrelated regulatory subunit ClpC1 of the ClpP protease as the molecular target of cyclomarin A in Mycobacterium tuberculosis . Thus, cyclomarin A is a rare example of a natural product with two distinct and specific modes of action. Abstract : Cyclomarin A is a potent hit in two phenotypic screens. It inhibits growth of M. tuberculosis through binding to ClpC1 as previously reported. Here we demonstrate that cyclomarin exerts its cidal activity against the malaria parasite Plasmodium falciparum through potent inhibition of the enzyme diadenosine triphosphate hydrolase (PfAp3Aase).